Research design considerations for randomized controlled trials of spinal cord stimulation for pain: Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials/Institute of Neuromodulation/International Neuromodulation Society recommendations. Issue 7 (July 2021) - Katz, Nathaniel; Dworkin, Robert H.; North, Richard; Thomson, Simon; Eldabe, Sam; Hayek, Salim M.; Kopell, Brian H.; Markman, John; Rezai, Ali; Taylor, Rod S.; Turk, Dennis C.; Buchser, Eric; et al.
Abstract : Abstract: Spinal cord stimulation (SCS) is an interventional nonpharmacologic treatment used for chronic pain and other indications. Methods for evaluating the safety and efficacy of SCS have evolved from uncontrolled and retrospective studies to prospective randomized controlled trials (RCTs). Although randomization overcomes certain types of bias, additional challenges to the validity of RCTs of SCS include blinding, choice of control groups, nonspecific effects of treatment variables (eg, paresthesia, device programming and recharging, psychological support, and rehabilitative techniques), and safety considerations. To address these challenges, 3 professional societies (Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials, Institute of Neuromodulation, and International Neuromodulation Society) convened a meeting to develop consensus recommendations on the design, conduct, analysis, and interpretation of RCTs of SCS for chronic pain. This article summarizes the results of this meeting. Highlights of our recommendations include disclosing all funding source and potential conflicts; incorporating mechanistic objectives when possible; avoiding noninferiority designs without internal demonstration of assay sensitivity; achieving and documenting double-blinding whenever possible; documenting investigator and site experience; keeping all information provided to patients balanced with respect to expectation of benefit; disclosing all information provided to patients, including verbal scripts; using placebo/sham controls when possible; capturing a complete set of outcome assessments; accounting for ancillary pharmacologic and nonpharmacologic treatments in a clear manner; providing a complete description of intended and actual programming interactions; making a prospective ascertainment of SCS-specific safety outcomes; training patients and researchers on appropriate expectations, outcome assessments, and other key aspects of study performance; and providing transparent and complete reporting of results according to applicable reporting guidelines. Abstract : Supplemental Digital Content is Available in the Text.